Stroke. Issue 10069 (11th February 2017) - Hankey, Graeme J
Summary: In the past decade, the definition of stroke has been revised and major advances have been made for its treatment and prevention. For acute ischaemic stroke, the addition of endovascular thrombectomy of proximal large artery occlusion to intravenous alteplase increases functional independence for a further fifth of patients. The benefits of aspirin in preventing early recurrent ischaemic stroke are greater than previously recognised. Other strategies to prevent recurrent stroke now include direct oral anticoagulants as an alternative to warfarin for atrial fibrillation, and carotid stenting as an alternative to endarterectomy for symptomatic carotid stenosis. For acute intracerebral haemorrhage, trials are ongoing to assess the effectiveness of acute blood pressure lowering, haemostatic therapy, minimally invasive surgery, anti-inflammation therapy, and neuroprotection methods. Pharmacological and stem-cell therapies promise to facilitate brain regeneration, rehabilitation, and functional recovery. Despite declining stroke mortality rates, the global burden of stroke is increasing. A more comprehensive approach to primary prevention of stroke is required that targets people at all levels of risk and is integrated with prevention strategies for other diseases that share common risk factors.